2008
DOI: 10.1124/jpet.108.143677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Erythromycin on Biological Activities Induced byClostridium perfringensα-Toxin

Abstract: Clostridium perfringens ␣-toxin, an important agent of gas gangrene with inflammatory myopathies, possesses lethal, hemolytic, and necrotic activities. Here, we show that ␣-toxininduced lethality in mice was inhibited by i.v. preadministration of erythromycin (ERM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 39 publications
(41 reference statements)
3
32
0
1
Order By: Relevance
“…These results show that the 14-ring and the 15-ring macrolides have inhibitory effects on the lethality of alpha-toxin, but the 16-ring macrolides do not. The result coincided with that reported previously (Oda et al 2008). …”
Section: The Effect On Alpha-toxin-induced Deathsupporting
confidence: 83%
See 3 more Smart Citations
“…These results show that the 14-ring and the 15-ring macrolides have inhibitory effects on the lethality of alpha-toxin, but the 16-ring macrolides do not. The result coincided with that reported previously (Oda et al 2008). …”
Section: The Effect On Alpha-toxin-induced Deathsupporting
confidence: 83%
“…Bunderen et al also found that the toxin-induced hemolysis is an additional prominent factor in the pathogenesis of septicemia caused by C. perfringens (van Bunderen et al 2010). We have reported the relationship between the toxin-induced hemolysis and activation of phospholipid metabolism via pertussis toxin-sensitive GTP-binding protein (Gi) (Sakurai, Ochi and Tanaka 1994, Ochi et al 1996, Ochi et al 2004, Oda et al 2008. Intravenous injection of alpha-toxin in mice resulted in massive intravascular hemolysis (Sugahara andOsaka 1970, Kreidl, Green andWren 2002).…”
Section: Effect On Systemic Hemolysis Induced By Alpha-toxinmentioning
confidence: 99%
See 2 more Smart Citations
“…However, penicillin and cephalosporin do not have such activity. Oda et al [49] have reported that erythromycin pretreatment reduces the release of TNF-α from activated neutrophils and suppresses hemolysis.…”
Section: Peer Reviewmentioning
confidence: 99%